Classism and dehumanization in chronic pain: a qualitative study of nurses inferences about women of different socio-economic status - Diniz, E.; Castro, P.; Bousfiled, A.; Bernardes, S.F. (British Journal of Health Psychology, 2020)
Objectives: Class-based dehumanization in health is poorly investigated. Beliefs about social class are often shared across cultures, with people of lower socio-economic status (SES) being typically dehumanized. This study specifically examined how nurses’ perceptions of pain patients’ SES were associated with (more or less) dehumanizing inferences about their pain and different treatment recommendations. Design: Sequential mixed methods including Similitude Analysis (statistical analysis of qualitative data) and a Thematic Analysis. Fifty female nurses watched short videos of two white women of different SES (low vs. middle) and similar levels of pain behaviours. Afterwards, nurses were asked to complete (1) a Free Association Task (associating characteristics and a profession to the women) and (2) a Story-Completion Task (writing a story describing women's lives, pain, and recommending treatments). Data were analysed with Similitude and Thematic Analysis. Results: The women's SES was recognized, linked to distinct professions, and associated with distinct inferences. The middle-SES woman was depicted with both Uniquely Human (e.g., autonomous) and Human Nature (e.g., communicative) traits, positive future prospects, and competence to self-manage pain. The low-SES woman was associated with Human Nature traits (hard-working) but denied Uniquely Human traits associated with competence; she was imagined as passive towards pain, with poor future prospects and referred to psychoeducation. Conclusion: Findings reveal the role of class-based cultural belief systems in pain care, showing how nurses’ recognition of low SES is associated with dehumanizing inferences and recommendations, which may contribute to reproducing pain care disparities. Theoretical implications of these findings for social and health psychology are drawn. Statement of contribution What is already known on the subject? • Psychosocial research on health and pain care disparities has paid more attention to the role of race/racism and gender/sexism than the role of social class/classism; Belief systems about social class are shared across cultures; people from lower SES are often dehumanized by being denied competence, civility, and self-determination; Class-based dehumanization may influence the relational and technical aspects of clinical encounters but little is still known about these processes. What does this study add? Drawing upon a mixed-methods approach, this study provides novel findings on class-based dehumanization inferences made by female nurses on female chronic pain patients; Nurses perceived the lower SES patient with fewer Uniquely Human traits, that is, less competent, with more pain-related disability, and recommended her more psychoeducation. Class-based dehumanization processes may contribute to reproducing pain care disparities and may prove to be important targets for intervention development.